DIMENSI GENDER DALAM KEHIDUPAN PENDUDUK LANSIA DI INDONESIA - Mohammad Yusuf (Populasi, 2007)
Retirement could become the golden moment in life for those who already prepared for it, but it could also become a disaster for those who did not. Retirement could be as the moment to relax, to enjoy the earning they made while they were still in their cariers. The preparation will be more needed for those elderly who did not have family or relatives. Sometimes they were forced to still go to work to make through the day. Many studies have been done to study the welfare of the eldery in preparing their retirement. Data for this paper was based from IFLS 3 which analized elderly gender dimension in Indonesia in their retirement. The theme will be coverd around jobs and health insurance, marriage life and living place pattern.